Language learning strategies used by undergraduates to overcome language and affective-related problems in speaking English / Hazlia Azila Illias - Hazlia Azila, Illias (2012)
A study was carried out to examine and to compare between the perceptions of the English-major and non-English-major University of Malaya students towards the problems they faced in speaking English and between the strategies they used to improve their spoken English. Specifically, the objectives of the study were to investigate and to compare between the English-major and non-English-major students‟ perceptions towards their language-related and affective-related problems in speaking English, and to examine and to compare between both groups‟ use of cognitive and functional-use strategies to improve their spoken English. The sample for the English-major population consisted of 30 students majoring in TESL, while the sample for the non-English-major population comprised 30 students majoring in various non-English-related Arts and Social Sciences programmes. The instrument used in this study was a questionnaire adapted from Rujipornwasin (2004) for the part on students‟ perceptions towards the problems, and from Nakanoko (2004) with reference to Oxford (1990) for the part on students‟ strategies use. The questionnaire consisted of 26 items for the section on perceptions towards problems, each one on a 5- point Likert scale ranging from „strongly agree‟ to „strongly disagree‟, and 30 items for the section on strategies use, each one on a 5-point Likert scale ranging from „always or almost always true of me‟ to „never or almost never true of me‟. Data analyses were performed with SPSS version 18.0 for frequency and percentage counts and manually for score counts. Interviews were conducted on 10 out of the 60 participants in order to validate the findings, to obtain additional information, or to gain a better understanding. Results from the study showed that the non-English-major students perceived themselves to have more problems in speaking English, and that the English-major students used the strategies for spoken English more frequently. Among the similarities shared by both groups were the perception that they mostly lacked vocabulary and a high use of „practising the sounds of English‟ strategy. One of the implications of the findings was the suggestion for the non-Englishmajor students to use more of the strategies employed by the English-major students since the English-major students perceived themselves to have fewer problems in speaking English.